Religiosity, religious coping and distress among outpatients with psychosis in Singapore - Cetty, Laxman (2023)
This study aimed to investigate the prevalence of religious coping and explore the association between religious coping, religiosity, and distress symptoms amongst 364 outpatients diagnosed with psychosis in Singapore. Positive and Negative Religious Coping (PRC and NRC), religiosity (measuring the constructs of Organised Religious Activity (ORA), Non-Organised Religious Activity (NORA), and Intrinsic Religiosity (IR)) and severity of distress symptoms (depression, anxiety and stress) were self-reported by the participants. The majority of participants (68.9%) reported religion to be important in coping with their illness. Additionally, multiple linear regression analyses found that NRC was significantly associated with higher symptoms of distress. In contrast, ORA was significantly associated with lower anxiety symptom scores. Overall, the study indicates the importance of religion in coping with psychosis and the potential value in incorporating religious interventions in mental health care.